# Expand this proof further: $\cot^2\theta + \sec^2\theta = \tan^2\theta + \csc^2\theta$

I am curious as to how one would prove this without changing both sides of the equation. In other words going straight from $$\cot^2\theta + \sec^2\theta$$ to $$\tan^2\theta + \csc^2\theta$$ (or vice-versa) rather than editing both sides to meet up at a certain point as I have done in my proof.

This is my proof:

$$\cot^2\theta + \sec^2\theta = \tan^2\theta + \csc^2\theta$$

LHS: $$=\frac{\cos^2\theta}{\sin^2 \theta} +\frac{1}{\cos^2\theta}$$

$$=\frac{\cos^4\theta + \sin^2\theta}{ \sin^2\theta \cos^2\theta}$$

RHS: $$=\frac{\sin^2\theta}{\cos^2\theta} + \frac{1}{\sin^2\theta}$$

$$= \frac{{(\sin^2\theta)}^2 + \cos^2\theta}{\sin^2\theta\cos^2\theta}$$

$$=\frac{(1-\cos^2\theta)^2 + \cos^2\theta}{\sin^2\theta\cos^2\theta}$$

$$=\frac{\cos^4\theta + \sin^2\theta}{\sin^2\theta\cos^2\theta}$$

-

\begin{align} \cot^2\theta + \sec^2\theta &=(\csc^2{\theta}-1)+(1+\tan^2{\theta})\\ &=\csc^2{\theta}+\tan^2{\theta} \end{align}

-
Laughing at myself now, I pretty much derived that earlier. Maybe I should sleep more. Thank you. – Kermit the Hermit Jun 16 '14 at 5:32

Take your sequence of expressions labelled "RHS", flip it over and append it to your sequence of expressions labelled "LHS". Delete the duplicate at the join.

-

Take difference of left hand side and right hand side of known identities and transpose:

$\sec^2\theta -\tan^2\theta = 1$

$\csc^2\theta -\cot^2\theta = 1$

-

Hint: Use the fact $\tan^2{\theta}=\sec^2{\theta-1}$ and $\cot^2{\theta} = \csc^2{\theta}-1$.

-

$$\csc^2 A-\cot^2A=1=\sec^2A-\tan^2A$$

-